Implementasi Sistem Antrian Jaringan Jackson Pada Rumah Sakit - Varisa Puspaningrum (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2016)
Meet the patient's expectation is one of the requirements in health care quality. In order to achieve the healthcare quality, hospitals need to change the paradigm from drug oriented to patient orientation. The main problem in health care quality today is patients waiting a long time for service and it will increase the morbidity risk and socioeconomic cost. A solution to resolve long service time is to implement a queuing system that can predict the actual queue situation. This study aim is estimating theÂ waiting time of patients using Network Queue Jackson Method. We build a queuing model with 8 single servers and consists of 4 health care facilities, a registration, 5 consultation points for the patient, a pharmaceutical, and a cashier. In this method uses rules First Come First Serve where consumers can move from one workstation to another workstation before leaving the system. Through the Network Queue Jackson, each server or node can provide independent services that it possible to analyze each node separately.